Inoculation Pneumonia Caused by Coagulase Negative Staphylococcus - Shi, Meng-meng; Monsel, Antoine; Rouby, Jean-Jacques; Xu, Yan-ping; Zhu, Ying-gang; Qu, Jie-ming (Frontiers in Microbiology, 2019)
Rationale Although frequently retrieved in tracheal secretions of critically ill patients on mechanical ventilation, the existence of pneumonia caused by coagulase-negative staphylococci (CoNS) remains controversial. Objective To assess whether Staphylococcus haemolyticus (S. haemolyticus) inoculated in mice’s trachea can infect normal lung parenchyma, increasing concentrations of S. haemolyticus were intratracheally administered in 221 immunocompetent mice. Methods Each animal received intratracheally phosphate-buffered saline (PBS) (n = 43) or live (n = 141) or inactivated (n = 37) S. haemolyticus at increasing load: 1.0 × 106, 1.0 × 107, and 1.0 × 108 colony forming units (CFU). Forty-three animals were sacrificed at 12 h and 178 were sacrificed at 36 h; 64 served for post-mortem lung histology, 157 served for pre-mortem bronchoalveolar lavage (BAL) analysis, and 42 served for post-mortem quantitative bacteriology of lung tissue. The distribution of biofilm-associated genes was investigated in the S. haemolyticus strain used in our in vivo experiment as well as among 19 other clinical S. haemolyticus strains collected from hospitals or nursing houses. Measurements and Main Results Intratracheal inoculation of 1.0 × 108 CFU live S. haemolyticus caused macroscopic and histological confluent pneumonia with significant increase in BAL white cell count, tumor necrosis factor-α (TNF-α), and macrophage inflammatory protein (MIP)-2. At 12 h, high concentrations of S. haemolyticus were identified in BAL. At 36 h, lung injury and BAL inflammation were less severe than at 12 h and moderate concentrations of species belonging to the oropharyngeal flora were identified in lung tissue. The inoculation of 1.0 × 106 and 1.0 × 107 CFU live S. haemolyticus caused histologic interstitial pneumonia and moderate BAL inflammation. Similar results were observed after inoculation of inactivated S. haemolyticus. Moreover, biofilm formation was a common phenotype in S. haemolyticus isolates. The low prevalence of the ica operon in our clinical S. haemolyticus strain collection indicated icaA and icaD independent-biofilm formation. Conclusion In immunocompetent spontaneously breathing mice, inoculation of S. haemolyticus causes concentration-dependent lung infection that spontaneously recovers over time. icaA and icaD independent biofilm formation is a common phenotype in S. haemolyticus isolates.